STATUS GIZI DAN TINGGI BADAN BERHUBUNGAN DENGAN LEMPARAN KE DALAM (THROW-IN) ATLET SEPAKBOLA - Amin, Nur (Sports Collaboration Journal, 2023)
Throwing in during a soccer game is one of the basic techniques that athletes need to have. To get long throw results, an athlete is required to have good arm muscle strength. Good muscle strength can be met if training and energy needs are met properly. Fulfillment of energy needs can be seen through nutritional status. This research aims to find out the relationship between nutritional status and height and the results of throw-ins in football athletes. This research is a descriptive correlation type using a cross sectional design. The sample in this study consisted of 15 Indonesian Young Football Academy football athletes using a total sampling technique to determine the number. Some of the instruments used in data collection include a microtoice to measure height and a weight scale to determine body weight and the body mass index formula used to calculate a person's nutritional status, a tape measure and a soccer ball to measure throw-in results. The data obtained were analyzed using the Spearman's Range Test (CI 95%) and regression test using Anova. The research results that have been obtained include that there is a relationship between nutritional status and throw-in results for football athletes with a p-value of 0.01 and there is a relationship between height and throw-in results with a p-value of 0.001. And together (nutritional status and height) are related to the throwing results of football athletes with a p-value of 0.02 and the determinant coefficient results are obtained with a value of R = 0.53. It can be concluded that nutritional status and body height are related to the results of throw-ins in football athletes. Abstrak Lemparan ke dalam pada saat permainan sepak bola adalah salah satu teknik dasar yang perlu dimiliki oleh atlet. Untuk mendapatkan hasil lemparan yang jauh, seorang atlet dituntut memiliki kekuatan otot lengan yang baik, kekuatan otot yang baik dapat terpenuhi apabila kebutuhan latihan dan energi terpenuhi dengan baik. Terpenuhinya kebutuhan energi dapat dilihat melalui status gizi yang dimiliki. Penelitian ini memiliki tujuan untuk mengetahui bagaimana hubungan antara status gizi dan tinggi badan dengan hasil lemparan ke dalam atlet sepakbola. Penelitian ini berjenis korelasi deskriptif dengan memakai rancangan cross sectional. Sampel dalam penelitian ini berjumlah 15 atlet sepakbola Indonesia Muda Football Academy dengan teknik total sampling dalam menentukan jumlahnya. Beberapa instrument yang digunakan dalam pengambilan data antara lain microtoice untuk mengukur tinggi badan dan timbangan berat badan untuk mengetahui berat badan serta rumus indeks massa tubuh digunakan untuk menghitung status gizi seseorang, meteran dan bola sepak untuk mengukur hasil lemparan ke dalam. Data yang diperoleh dianalisis menggunakan uji korelasi Spearman’s Range Test (CI 95%) dan uji regresi menggunakan Anova. Hasil penelitian yang telah didapat antara lain terdapat hubungan antara status gizi dengan hasil lemparan ke dalam atlet sepakbola dengan nilai p-value 0,01 dan terdapat hubungan antara tinggi badan dengan hasil lemparan ke dalam dengan nilai p-value 0,001. Serta secara bersama-sama (status gizi dan tinggi badan) berhubungan dengan hasil lemparan atlet sepakbola dengan nilai p-value 0,02 dan didapatkan hasil koofesien determinan dengan nilai R = 0.53. Dapat disimpulkan bahwa status gizi dan tinggi badan berhubungan dengan hasil lemparan ke dalam atlet sepakbola.